Chemical synthesis of oligonucleotides using acetone as a washing solvent - Paul Gaytán (BioTechniques)
Acetone is being proposed as the main washing solvent during automated synthesis of oligonucleotides to reduce acetonitrile usage in the assembly process and endure the impact of global acetonitrile shortage.